Analisis Pembuatan BBA dan Uji Konsumsi Bahan Bakar dari Kombinasi Pirolisis Limbah Plastik Jenis LDPE & Kolam POME (Fat Pit) - Aprizal Aprizal; Wanda Laksana (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
LDPE (Low-Density Polyethylene) Plastic Waste, Is a type of plastic that is difficult to decompose and can pollute the environment in the long term. On the other hand, POME is waste from palm oil processing that contains high organic matter and can damage the ecosystem if not managed properly. This gave rise to the idea for the author that the pyrolysis process is an effective method to convert it into alternative fuel (BBA). This study also aims to find out how the pyrolysis process, as well as the results of physical tests and performance tests of BBA produced from LDPE plastic waste and POME palm oil mill waste. In this study using the experimental method (Pyrolysis) then after the pyrolysis process was successfully carried out and obtained BBA, then BBA was used for testing fuel consumption in vehicles